RELEVANSI AL-QUR’AN TERHADAP ILMU PENGETAHUAN MODEREN - Syahrul Jamil; Ali Akbar (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
The advancement of modern science has profoundly influenced human civilization in various aspects, including technology, culture, and social structure. However, this progress also raises philosophical and ethical questions regarding the role of religion in scientific inquiry. In the Islamic context, the Qur’an serves not only as a source of moral and spiritual guidance but also as a text that strongly encourages intellectual engagement. Through its verses, the Qur’an invites humanity to employ reason in comprehending the signs of God’s greatness manifested in the universe (ayat kauniyyah). This study aims to explore the relevance of the Qur’an to modern science by analyzing the interrelationship between divine revelation and scientific methodology. The research adopts a qualitative descriptive approach through library research, drawing upon classical and modern Qur’anic exegesis, Islamic philosophy of science, and contemporary academic works. The analysis seeks to reveal how the Qur’an affirms observation, reflection, and reasoning as essential means to understand both divine truth and empirical reality. The findings demonstrate that the Qur’an remains profoundly relevant to modern scientific thought, as both are rooted in the pursuit of truth. Although the Qur’an is not a scientific textbook, its contents provide moral inspiration and epistemological foundations for scientific inquiry. Ethical values such as honesty, accountability, and sincerity constitute essential principles of scientific activity in Islam. Therefore, the integration of Qur’anic principles with modern science is necessary to ensure that scientific progress continues to serve humanity while remaining aligned with spiritual and ethical values.